Accurate method for evaluating the duration of the entire radiotherapy process - Guo, Chenlei (J Appl Clin Med Phys, 2020)
BACKGROUND AND PURPOSE: Along with the increasing demand for high‐quality radiotherapy and the growing number of high‐precision radiotherapy devices, precise radiotherapy workflow management and accurate time evaluation of the entire radiotherapy process are crucial to providing appropriate, timely treatment for cancer patients. This study therefore aimed to establish an accurate, reliable method for evaluating the duration of the radiotherapy process, from beginning to end, based on real‐time measurement data. These data are vital for improving the quality and efficiency of radiotherapy delivery. MATERIALS AND METHODS: Altogether, 17 620 cancer patients’ radiotherapy experiences were measured in real time in our radiation oncology department. The process was divided into five sequential core modules, with the start and stop times of each module automatically recorded using MOSAIQ software, an automated radiotherapy management system. The duration for each module and the total duration of the entire process were then automatically calculated and qualitatively analyzed. RESULTS: The analysis showed significant treatment–time differences depending on the tumor site, which provided a practical reference for improvement of previous treatment modules and appointments management. In all, >60% of the cancer patients’ total treatment time could be shortened. CONCLUSIONS: We established a reliable method for evaluating the overall duration of radiotherapy protocols. The results pointed out a clear pathway by which we could improve future radiotherapy workflow management and appointment systems.